Study on inner corrosion behavior of high strength product oil pipelines. (September 2020) - Wang, Zhengquan; Zhou, Ziyang; Xu, Weichen; Yang, Lihui; Zhang, Binbin; Li, Yantao
Graphical abstract: Schematic model of corrosion causes and failure mechanisms on the inner wall of the product oil pipeline. Highlights: The inner corrosion behavior of high strength product oil pipelines was studied, and some new ideas were put forward. The three pipeline steels have the same corrosion mechanism. X80 pipeline steel has better adaptability under the condition of corrosion in the product oil pipeline. It is more practical to accelerate the development of X80 pipeline steel to make it more applicable to the construction of the product oil pipelines. Abstract: Pipeline transportation is one of the five major modes of transportation. Inner corrosion problems in product oil pipelines are widespread but have not received attention, and high strength product oil pipelines are rarely used in China. In this paper, morphology and composition analysis and electrochemical methods were used to study the corrosion behaviors and characteristics of API 5L X65, X70 and X80 steel product oil pipelines. The feasibility of using high strength product oil pipelines in the transportation environment of product oil under the condition of inner corrosion is discussed, and the support for the safe operation of product oil pipelines is provided. The research results show that X80 pipeline steel has advantages over X65 and X70 pipeline steel. In the simulated liquid system of sediments in product oil pipeline, as the immersion time increases, the corrosion rate of X65, X70 and X80 pipeline steels shows a trend from high to low. Morphological analysis and electrochemical analysis showed that X80 pipeline steel showed better performance and adaptability to the environment, and its aerobic corrosion reaction was slower than that of X65 and X70 pipeline steel. X-ray photoelectron spectroscopy (XPS) results show that the three pipeline steels have the same corrosion mechanism, and all of them form Fe2 O3, FeOOH, FeCO3, and FeS. The corrosion process is similar but the speed is different. This is attributed to the more corrosion-resistant trace elements in the X80 pipeline steel composition and the structure more compact. The application of high strength API 5L X80 steel in the product oil pipeline is still in its infancy, and it will be more practical to accelerate the development of API 5L X80 steel to make it more applicable to the construction of product oil pipelines.